Estudo da correlação da densitometria óssea e do perímetro diafisário medial do terceiro metacarpiano em equinos - Aguiar, A. C. S. [UNESP]; Machado, Vania Maria de Vasconcelos [UNESP]; Santos, R. V. [UNESP]; Puoli Filho, J. N. P. [UNESP]; Mota, M. D. S. [UNESP]; Vulcano, Luiz Carlos [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2012)
In this study, 14 post mortem equine metacarpal bones were evaluated to correlate the medial III metacarpus perimeter to dorsal bone density of the same region using Computed Tomography and Quantitative Ultrasound (QUS). According to Pearson's test, there were not correlations between these variables. Considering there are few bone densitometry studies in horses and there are many variables that can interfere with bone mineralization, new studies on equine bone density applying standard variables are recommended.
Correlation study on equine bone densitometry and third metacarpus diaphyseal perimeter
Keywords: ultrassonografia quantitativa; equinos; terceiro metacarpiano; quantitative ultrasound; equine; third metacarpal